Hydraulic performance characteristics of impact sprinkler with a fixed water dispersion device - Issaka, Zakaria; Li, Hong; Jiang, Yue; Tang, Pan; Chen, Chao; Darko, Ransford Opoku (International Journal of Agricultural and Biological Engineering, 2018)
One way to adapt to the trend towards low-energy and to improve the hydraulic performance of the impact sprinkler under a low pressure condition is by means of a fixed water dispersion device. A fixed dispersion device disperses jet flow from the nozzle continuously. The shape of the tip, impact angle (θ), diameter (D), and depth in the jet flow (d) have significant influence on the hydraulic performance. In this study, the hydraulic performance characteristics of impact sprinkler as affected by the fixed water dispersion device were studied under indoor conditions. Radial water distributions from the sprinkler were obtained by experiments for the fixed water dispersion devices. MATLAB was used to transform the radial data into net data, and the uniformities were simulated in a square layout from 1 to 2 times the range (R). The droplet size distributions from the fixed water dispersion devices were measured by a laser precipitation monitor (LPM). Results showed that the range increased with the increase of pressure, and the sprinkler with type C2 produced a rectangular-shaped water distribution pattern, while the range was maintained. A maximum uniformity of 71.56%, 75.56%, 77.23%, 73.32%, 78.88% and 86.67% was found for types A1, B1, C1, A2, B2, and C2, respectively under a pressure of 200 kPa. The uniformity from the sprinkler using type C2 surpassed 80%, while type C1 fell below. Droplet sizes from type C2 was best, and the mean droplet diameter decreased with the increase of pressure. Hence, type C2 can be selected for further optimization of the design features to improve the hydraulic performance of the impact sprinkler under low pressure conditions. Keywords: fixed water dispersion device, impact sprinkler, range, water distribution, uniformity, droplet size DOI: 10.25165/j.ijabe.20181106.4026 Citation: Issaka Z, Li H, Jiang Y, Tang P, Chen C, Darko R O. Hydraulic performance characteristics of impact sprinkler with a fixed water dispersion device. Int J Agric & Biol Eng, 2018; 11(6): 104–112.